2007
DOI: 10.1212/01.wnl.0000291618.32247.2d
|View full text |Cite
|
Sign up to set email alerts
|

Thickening in the somatosensory cortex of patients with migraine

Abstract: Objective-To examine morphologic changes in the somatosensory cortex (SSC) of patients with migraine.Methods-Cortical thickness of the SSC of patients with migraine was measured in vivo and compared with age-and sex-matched healthy subjects. The cohort was composed of 24 patients with migraine, subdivided into 12 patients who had migraine with aura, 12 patients who had migraine without aura, and 12 controls. Group and individual analyses were performed in the SSC and shown as average maps of significant change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
203
3
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 230 publications
(224 citation statements)
references
References 37 publications
(35 reference statements)
16
203
3
2
Order By: Relevance
“…Probably neuroimaging will guide the way here as further exploration of the pain matrix within the central nervous system and their connectivities are elucidated [15]. Already important work has been done to show that there are obviously functional changes in the cortex, subcortical and brainstem structures and there are significant volumetric changes in the cortex of the migraine brain [16]. Functional changes are seen in the visual cortex in migraine [17], and in chronic migraine there appears to be some degree of reversibility particularly after overuse of medication is reversed [18].…”
Section: Discussionmentioning
confidence: 99%
“…Probably neuroimaging will guide the way here as further exploration of the pain matrix within the central nervous system and their connectivities are elucidated [15]. Already important work has been done to show that there are obviously functional changes in the cortex, subcortical and brainstem structures and there are significant volumetric changes in the cortex of the migraine brain [16]. Functional changes are seen in the visual cortex in migraine [17], and in chronic migraine there appears to be some degree of reversibility particularly after overuse of medication is reversed [18].…”
Section: Discussionmentioning
confidence: 99%
“…With the extensive direct and indirect connectivity of the numerous cortical regions with the mesolimbic pathway, it is not surprising that stress and illness can affect reward and motivational behavior [56,57]. Research has demonstrated altered cortical structure and function following migraine attacks [58][59][60][61], and thus represents one likely pathway by which migraine, stress, the accompanying negative affect, and altered motivational states are intimately linked.…”
Section: Anterior Cingulate Cortex In Pain and Rewardmentioning
confidence: 99%
“…New findings from extensive functional imaging studies on central pain networks allowed the identification of patterns of cortical and brainstem activation in some way ''specific'' for different primary headache subtypes [12][13][14]. In addition, structural alterations (either as hypertrophic or hypotrophic changes) of these areas have been consistently reported in headache series [15,16] as well as in other chronic pain syndromes [17][18][19] leading to the assumption that the repeated activation of the pain networks may promote neuroplastic cortical changes causing a permanent facilitation of pain signals, ultimately leading to the chronicisation of pain [20].…”
Section: Cortical Spreading Depression and Migrainementioning
confidence: 99%